Immediate care of school sport injury. Issue 3 (9th September 2003) - Abernethy, L; MacAuley, D; McNally, O; McCann, S
Abstract : School sport is a major cause of injury in the post-primary age group. The importance of primary prevention in sport has been identified; however secondary prevention of school related sport injury has not been described in Ireland. A random sample of 450 schools in Northern Ireland and the Republic of Ireland was studied using a postal questionnaire. Current management of sport injury, with particular interest in the expertise and training of teachers and coaches, was explored. Replies were received from 333 (74%) schools. There was no physical education teacher with up to date first aid training in 37% schools. Immediate care in terms of mechanisms and equipment to deal with injury was available in 35%–81% of schools responding. Correct response ranged from 65%–90% to four scenarios: commonly presenting yet potentially serious management problems. This study demonstrated deficiencies in sport injury care. In addition to concern about current training, a need for basic life support training is highlighted. These findings have implications for the prevention of school sports injuries.